Karbon Tersimpan Pada Tegakan Benih Teridentifikasi “Pambelum” di Kota Palangka Raya - Hanafi, Nanang (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2019)
This study was carried out on a single observation plot measuring 20 m x 100 m in the Tegakan Benih Tersertifikasi (TBT) “Pambelum in Palangka Raya City to determine of carbon stocks in five carbon sources. The method used in this study is destructive methods to determine the amount of carbon stocks in litter, and understorey, non-destructive to measure carbon stocks in tree biomass, woody necromass, and roots. Total carbon stored in TBT Pambelum is 196.695 tons / ha, where tree biomass contributes carbon at 62.67% (123.264 tons / ha); rooting contributes carbon at 23.19% (45.608 tons/ha); carbon deposits on land at 12.34% (24,281 tons/ha); litter of 1.34% (2.736 tons/ha); understorey of 0.40% (0.785 tons/ha); and woody necromass of 0.01% (0.020 tons/ha).